Aortic allografts in treatment of aortic valve and ascending aorta prosthetic endocarditis - S.V. Spiridonov (Кардіохірургія та інтервенційна кардіологія)
The aim – to assess short- and long-term results of aortic root replacement using aortic allografts in patients with prosthetic endocarditis. Materials and methods. Since February 2009 until June 2016 aortic valve and ascending aorta replacement using aortic allografts was performed in 26 patients with prosthetic endocarditis. In 50 % of cases at initial operation aortic valve replacement was performed, in another 50 % of cases – aortic valve and ascending aorta replacement. Echocardiography was performed 10 days, 3, 6 and 12 months, 2, 3 and 5 years after surgery. Analysis of long-term results included all cases of deaths, prosthesis-related complications and recurrence of endocarditis. Results. 30-day mortality was 23.1 %. Extracorporeal membranous oxygenation (ECMO) was used only in 5 patients (19.2 %). Four patients were weaned from ECMO. We did not observe any allograft-related complications. During follow-up period there were no cases of reoperation due to structural allograft failure. Relapse of infection occurred in 1 patient (3.8 %) four years after the operation and led to lethal outcome.